Analisis Wacana Free West Papua Campaign pada Operasi Militer Indonesia dalam Konflik Nduga: Sebuah Tinjauan Kritis - Rumila, Diana Nur; Effendi, Yusli (Department of International Relations, Brawijaya University, 2020)
Mainstream narratives on Indonesia's military operation in West Papua describe it to help the conflicting region achieve peace and prosperity. This hegemonic and widely held public opinion is more often used to justify the behavior of the Indonesian Government in West Papua. This research aims to offer an alternative perspective on the matter by looking at the narrative promoted and written by Free West Papua Campaign (FWPC) on their news reports about the Nduga Conflict in 2018-2019 from their website: freewestpapua.org. Norman Fairclough's critical discourse analysis examines the discourse created from the news coverage within the three-dimensional analysis, namely the textual, the discourse practices, and sociocultural dimensions. Results show that FWPC depicts Indonesia's military as exploiters of the indigenous Papuans. At the same time, FWPC also tries to build a sense of belonging to gain support from the international society and online activists.